The place of art: between the uninhabited sky and the Cross. (An interpretation based on the Phenomenology of Spirit) - Fallas Fernández, Daniel (2025)
This article deals simultaneously with a historical and a textual gap. The first corresponds to the moment between the dissolution of the Greek world and the establishment of the Christian world. The second corresponds to the moment between «art-religion» and the «manifested religion» in Hegel's Phenomenology of Spirit (1807). Both gaps are thought of in close connection with the problem of the autonomy of art; which, in order to exist, prefigures a place. Following Jean-Luc Nancy, it is concluded that this place corresponds to the periods of immanence, of which there are above all two: Late Antiquity and Modernity.